The Future of Research in Strategy Implementation in the BRICS Context - Geovana Alves de Lima Fedato; Vanessa Martins Pires; Guilherme Trez (BBR: Brazilian Business Review)
Albeit the development of the capacity to implement strategic change being a challenge to modern organizations, the studies in this area have prioritized intern issues of the organization, relegating it as a secondary plan, the contextual factors. Implementing a new strategy implies in the alignment of resources and internal capabilities to the organizational reality, adjusting them to the needs or external impositions. Thus, this study aims to identify research suggestions on strategy implementation and relate them to the characteristics of the countries belonging to the BRICS, through a systematic review. In order to meet this goal, the coevolution perspective was used to support the discussion of strategy implementation, stimulating reflections on the role of management and the environment in the context of strategic change. Academically speaking, the results point to an update on the research agenda on implementation strategy; at the managerial level, we present insights for managers of companies operating or that intend to settle in the BRICS countries.